Synthesis of (2S,3R)-3-amino-2-hydroxydecanoic acid and its enantiomer: a non-proteinogenic amino acid segment of the linear pentapeptide microginin - Rohokale, Rajendra S.; Dhavale, Dilip D. (Beilstein Journal of Organic Chemistry, 2014)
A directed manipulation of the functional groups at C3 and C4 of D-glucose was demonstrated to synthesize naturally occurring (2S,3R)-α-hydroxy-β-aminodecanoic acid (AHDA, 2a) and its enantiomer 2b. The enantiomer of 2a is the N-terminal part of the natural linear pentapeptide microginin, which is used as an antihypertensive agent.
Keywords: AHDA; carbohydrate; chiron approach; enantioselective; natural products; non-proteinogenic amino acid